HUBUNGAN ANTARA SOKONGAN SOSIAL DAN KESIHATAN MENTAL DALAM KALANGAN KAKITANGAN JABATAN AGAMA ISLAM MELAKA (JAIM) - Dzalin, Nurul Marshitah; Yusof, Faudziah (Jurnal ’Ulwan, 2023)
This study aims to look at the relationship between social support and mental health among the staff of the Islamic Religious Department Malacca (JAIM). A total of 86 male and female staff were selected by simple random sampling. The questionnaires used were the Inventory Of Social Support Behavior (ISSB) to measure the level of social support and the General Health Questionnaire-12 (GHQ-12) to measure mental health. All data obtained were analyzed using Statistical Package For The Social Sciences (SPSS) version 26. This study involved descriptive and inferential analysis using correlation, t-test and ANOVA. The results of the study found that there was no significant relationship between social support and mental health among JAIM staff [r = .984, k> .05]. In addition, the results of the study also showed that there was no difference in mental health based on gender [t (-2.245) = .0.27, k> .05]. However, the results of the analysis also found that there are differences in mental health based on age [F (2, 83) = .110, k > .05]. In conclusion, future studies are proposed to increase the number of samples based on the study population. Next, the research questionnaire can be distributed by face to face to produce a better research results.